1982
DOI: 10.1139/m82-044
|View full text |Cite
|
Sign up to set email alerts
|

The differential susceptibility of gonococcal opacity variants to sex hormones

Abstract: Neisseria gonorrhoeae exist in transparent (Tr) and opaque (Op) colony forms. Op forms are recovered from patients early in the menstrual cycle; Tr colonies predominate late in the cycle. The mechanism for this colonial variation was examined by determining the influence of gonodal hormones on growth inhibition of Op and Tr isogenic variants of gonococci. The estrogens, estrone and estradiol, enhanced growth whereas 19-nortestosterone, testosterone, and progesterone significantly inhibited gonococcal growth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…P.ll proteins of N. gonorrhoeae have been correlated with increased adherence to buccal epithelial, oonjunctival and phagooytic cells (Bessen and Gotschlich, 1986;Heckels, 1982;Lambden ef al., 1979;Virji and Heckels, 1986;King and Swanson, 1978), autoaggregation (Swanson, 1978a;Swanson, 1982), altered serum resistance (Lambden et al, 1979), and resistance to certain antibiotics (Lambden et ai., 1979) and steroid hormones (Salit, 1982). Less is known about the Class V proteins of N. meningitidis, although it is thought that they may play similar roles (Kawulaef a/., 1988;Stern and Meyer, 1987;Tsai et ai., 1981).…”
Section: Introductionmentioning
confidence: 99%
“…P.ll proteins of N. gonorrhoeae have been correlated with increased adherence to buccal epithelial, oonjunctival and phagooytic cells (Bessen and Gotschlich, 1986;Heckels, 1982;Lambden ef al., 1979;Virji and Heckels, 1986;King and Swanson, 1978), autoaggregation (Swanson, 1978a;Swanson, 1982), altered serum resistance (Lambden et al, 1979), and resistance to certain antibiotics (Lambden et ai., 1979) and steroid hormones (Salit, 1982). Less is known about the Class V proteins of N. meningitidis, although it is thought that they may play similar roles (Kawulaef a/., 1988;Stern and Meyer, 1987;Tsai et ai., 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The factors responsible for the observed associations between Opa phenotype, culture rate, and the menstrual cycle are not known. Salit (49) showed that opaque colonies were more resistant to progesterone than transparent colonies; however, the resultant hypothesis that Opa proteins directly protect gonococci from progesterone was not supported when gonococci with defined Opa phenotypes were tested (52). It is possible that the expression of Opa protein colonization receptors is hormonally regulated.…”
mentioning
confidence: 99%
“…Gonococci expressing PII proteins are generally isolated from infections localized to the surface mucosa, whereas organisms recovered from disseminated infections often lack PII proteins (6,7). The possession of certain PII proteins has been associated with resistance to antibiotics and steroid hormones (12,19), altered-serum resistance (8,12), increased sensitivity to serum proteases (2), and increased adherence to buccal epithelial cells (12) and phagocytic cells (18).…”
mentioning
confidence: 99%